HOW DOES THE INSTAGRAM-SOCIAL MEDIA USE WITH MINDFUL CONSUMPTION AFFECT TO EMOTIONAL INTELLIGENCE OF BUDDHIST STUDENTS IN HIGH SCHOOL? - Tri Anggraini; Komang Sutawan; Burmansah Burmansah (Jurnal Scientia, 2023)
Using applications on social media can make it easier for students to establish communication in cyberspace, such as Instagram social media. However, if you look at the current sit researchers have done, social media has not been done well. Based on the conservation researchers have done, problems arise such as 2.2% difficulty in recognizing self-emotions, 6.7% difficulty in overcoming self-emotions, 15.6% difficulty in motivating themselves, 22.2% difficulty in empathy, and 13.3% difficulty building relationships. The purpose of this study was to find 1) whether there is an influence of Instagram social media use with conscious consumption on emotional intelligence and 2) how much influence Instagram social media use with conscious consumption has on emotional intelligence. This research uses a quantitative approach with survey methods. The population of this study amounted to 55 respondents, with a whole population study. The study was conducted at Xaverius 1 Junior High School Bandar Lampung with respondents of Buddhist students. The study results illustrate a significant influence between the variable use of Instagram social media and conscious consumption of emotional intelligence. The criterion for hypothesis testing is to reject H0 if t count > t table and vice versa. For the distribution t used dk = (n-2) and α = 0.05. Based on data analysis, t count = 3.049 while t table with n = 55 and α = 0.05 obtained 1.673. Then, it can be known that t count > t table (3.049 ≥ 1.673) or sig (0.004 < 0.05). So, it can be concluded that H0 is rejected and Ha is accepted, so there is an influence between the use of Instagram social media and the conscious consumption of emotional intelligence of Buddhist students in high schools.